Master Plan and Environment: What Has Been Researched on the Topic? - Azevedo, Mariana Emilene Arruda; Rodovalho, Sarah Afonso; Oliveira, Lucimara Albieri de (Scientific Journal ANAP, 2025)
Objective – To analyze how the relationship between Master Plans and environmental issues has been addressed in Brazilian academic literature in the post-City Statute period (2001), identifying trends, gaps, and challenges in integrating urban planning and sustainability. Methodology – A quantitative-qualitative meta-study was conducted, examining 33 scientific articles indexed in SciELO, based on content analysis (Bardin, 1977) and thematic categorization. Originality/Relevance – The study fills a theoretical gap by systematizing academic research on the interface between Master Plans and the environment in Brazil, highlighting the persistent disconnect between legal frameworks and their practical application. The relevance lies in the urgency to improve urban policies to mitigate socio-environmental damage. Results – The findings revealed: a predominance of risk management-focused studies; criticism of municipal administrations for prioritizing the real estate market over environmental guidelines; a concentration of studies in the South and Southeast regions, neglecting other Brazilian regions; and a lack of interdisciplinary approaches to assess the effectiveness of public policies. Theoretical/Methodological Contributions – Critical systematization of academic research on the topic. Social and Environmental Contributions – The study highlighted the need for better integration between urban and environmental planning to reduce socio-environmental impacts and recommended overcoming bureaucratic obstacles in adopting more integrated and sustainable public policies in municipalities.